Primary care treatment of insomnia: study protocol for a pragmatic, multicentre, randomised controlled trial comparing nurse-delivered sleep restriction therapy to sleep hygiene (the HABIT trial) - Kyle, S; Madigan, C; Begum, N; Abel, L; Armstrong, S; Aveyard, P; Bower, P; Ogburn,E; Siriwardena, N; Yu, LM; Espie, C (BMJ Publishing Group, 2020)
Introduction Insomnia is a prevalent sleep disorder that negatively affects quality of life. Multicomponent cognitive-behavioural therapy (CBT) is the recommended treatment but access remains limited, particularly in primary care. Sleep restriction therapy (SRT) is one of the principal active components of CBT and could be delivered by generalist staff in primary care. The aim of this randomised controlled trial is to establish whether nurse-delivered SRT for insomnia disorder is clinically and cost-effective compared with sleep hygiene advice.